Comparative study of propofol and etomidate as intravenous induction agents for general anesthesia: hemodynamic effects, adrenal suppression, and blood glucose response in controlled hypertensive patients - Raina, Parul; Gulati, Smriti; Chauhan, Vrinda; Vig, Anita (International Journal of Research in Medical Sciences, 2023)
Background: General anesthesia induces unconsciousness and loss of reflexes, facilitating complex medical treatments. The induction of anesthesia is crucial for patient comfort and procedural success, with propofol and etomidate being common intravenous induction agents. Propofol offers a rapid onset and short duration, while etomidate is known for cardiovascular stability. Methods: A prospective randomized controlled trial involving 100 controlled hypertensive patients compared propofol and etomidate for induction. Hemodynamic parameters and biochemical responses were monitored at various intervals. Injection site discomfort and myoclonus were assessed, and cortisol and glucose levels were measured. Results: Baseline hemodynamic values were similar. Etomidate resulted in stable hemodynamics as compared to propofol. Blood sugars were comparable. Though serum cortisol levels were reduced after etomidate was given. But it came back to normal range 24 hours after surgery. Injection site pain was reported by 20% of etomidate patients and 10% of propofol patients. No myoclonus occurred. Conclusions: Etomidate is an effective induction agent for controlled hypertensive individuals, causing transient adrenal suppression without affecting blood sugar levels.